Quelques réflexions sur l’Accord de Paris et la souveraineté économique des États - Sophie Lavallée (VertigO)
The adoption of the Paris Agreement ended several years of negotiations under the United Nations Framework Convention on Climate Change to reach a consensus on a new protocol that would break with the binary approach to the Kyoto Protocol, demanding commitments from all developed and developing countries. To meet this challenge, does the agreement - both in form and content - limit the exercise of the economic sovereignty of the Parties? The present text takes a look at the Paris Agreement in terms of economic sovereignty, a natural extension of national sovereignty that must first be explored, before examining the space accorded to it by the Paris Agreement, especially for developing countries, whose development is a priority highlighted in the preamble of the Agreement.